Optimizing the Implementation of Podcast-Based Media to Improve Students' Speaking Skills Confidence - Nasution, Melina Putri Septiani; Saragih, Mandra (research, training and philanthropy institution Natural Aceh, 2025)
This study investigated the implementation of podcast-based media in improving students' confidence in speaking English at Darul Maaref School Foundation in Satun, Thailand. Using Classroom Action Research methodology, the study involved 30 eighth-grade students who initially demonstrated low speaking confidence, with 70% receiving incomplete grades. The research was conducted in two cycles following Burns' model: planning, implementation, observation, and reflection. Data collection included speaking tests and classroom observations focusing on language, pronunciation, attitude, and clarity. The results showed a significant increase in students' speaking confidence, with the average score increasing from 52 in the pre-cycle to 63 in Cycle I (11% increase) and 87 in Cycle II (24% increase), representing a total increase of approximately 62%. Observations of student activity also increased from 77% engagement in Cycle I to 92% in Cycle II. These findings suggest that podcast-based media addresses common challenges in speaking skill development, including speaking anxiety, by providing a flexible, engaging, and less intimidating platform. This research contributes to an innovative pedagogical approach that responds to contemporary educational needs in English language teaching and offers teachers a practical tool to improve students' speaking confidence in a 21st-century global context.